The characteristics of the microflora species composition and its antibiotic resistance in adult patients at cardiac surgery department - Varbanets, S. V.; Furman, M. M.; Marchenko, O. Y.; Filonenko, G. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The most important component of the prevention of infectious complications (IС) in patients undergoing cardiac surgery is the determination of the carrier state of opportunistic pathogenic microflora (OPM) from the admission and the identification of risk factors and comorbidity. For effective antibiotic prophylaxis, it is necessary to take into account the levels of natural resistance and the continuous growth of the acquired resistance of the OPM, especially the Enterobacter spp., producing ESBL (extended spectrum beta-lactamases). Purpose of the study – determine the features of the species composition of the microflora of the mucous membranes and their antibiotic resistance in adults at the admission to the cardiac surgery department. Material and methods. 109 patients treated in GI “CPCCC MHC in Ukraine” during the period from April to June 2018 were performed blood cultures. Results and discussion. The results of performed bacteriological studies showed that in most cases in samples of biological materials of the respiratory tract were identified Staphylococcus aureus. The second place were taken by Staphylococcus epidermidis – 57 (26.0%), Staphylococcus haemolyticus – 15 (6.1%). Among catalase-negative cocci, the most common were Streptococcus spp. – 40 (18.3%) and Enterococcus spp. – 5 (2.3%). Also the next strains of microorganisms were cultured: the gram-positive rods Corynebacterium spp. – 2 (0.9%) and Bacillus spp. – 3 (1.4%). From the 10 tested antibiotics, cefuroxime (II generation cephalosporin) demonstrated the lowest activity against Klebsiella pneumoniae strains with resistance of 81.8% (95%, CI 47.7–96.8). Conclusions. Our analysis shows that the preoperative detection of the patient’s microflora and the determination of antibacterial sensitivity could prevent the development of infectious complications and reduce the level of methicillin-resistant forms of microorganisms. The analysis of the etiological structure showed that staphylococci are the most common pathological agents in the upper respiratory tract.